Recent evolutionary history of Chrysoperla externa (Hagen 1861) (Neuroptera: Chrysopidae) in Brazil - Morales-Correa e Castro, Adriana C. [UNESP]; Chiarini Pena Barbosa, Nara Cristina [UNESP] (Public Library Science, 2017)
This work aimed to elucidate the distribution of Chrysoperla externa haplotypes and investigate whether it exhibits structure based on genetic composition as opposed to geographic location. The genetic diversity of C. externa, analyzed by AMOVA using the COI and 16S rRNA genes as mitochondrial markers, showed significant haplotype structure arising from genetic differences that was not associated with sampling location. This was reflected in the network grouping. Bayesian inference showed that haplotype distribution may have its origins in C. externa divergence into two distinct clades, which dispersed to various locations, and their subsequent diversification. The evolutionary history of C. externa may include multiple ancestral haplotypes differentiating within the same geographic area to generate the current broad genetic diversity, so that the earlier geographical history has been erased, and now we have highlighted its more recent genetic history.